Discriminating value of total minor physical anomaly score on the Waldrop scale between patients with bipolar I disorder and normal controls - Sivkov, Stefan; Akabaliev, Valentin; Mantarkov, Mladen; Ahmed-Popova, Ferihan; Akabalieva, Katerina (Psychiatry research, 2013)
Minor physical anomalies (MPAs) are slight structural aberrations indicative of abnormal neurodevelopment. Most studies of MPAs in bipolar disorder have yielded limited results. We attempted to assess the potential value of MPAs as a classifying test in the status bipolar I patients vs. normal controls. Sixty one bipolar I patients and 103 controls were evaluated for MPAs using a slightly modified version of the Waldrop scale. The specificity, sensitivity and predictive value of different total MPA (MPA-T) scores were determined. The cut-off MPA-T scores that optimally discriminated patients from controls (exhibiting the most balanced sets of sensitivity, specificity, positive and negative predictive values) were MPA-T≥4 and MPA-T≥5. These values set a “border zone” in which bipolar I patients began to prevail significantly over controls. The latter presented most frequently with MPA-T ≤3 and rarely with MPA-T ≥6. Bipolar I patients prevailed among outliers (subjects with significantly higher MPA-T scores). Our data establish MPA-T score as a reliable index in distinguishing between bipolar I patients and normal controls and are consistent with the hypothesis of abnormal neurodevelopment in bipolar disorder.